Hubungan Tingkat Pengetahuan Dan Status Pekerjaan Dengan Pemberian Asi Eksklusif - Septyasrini, Nurul; Rahayuningtyas, Faizah Betty (Universitas Muhammadiyah Surakarta, 2018)
Infancy and toddler be a good time for growing children. The provision of adequate nutrition into maternal and family obligations to support the growth of children. Nutrition is the most appropriate given to babies is breast milk. Exclusive breastfeeding for infants 0-6 months has been recommended by the WHO (World Health Organization), UNICEF (United Nation Childrens Fund), and Depkes RI (Departemen Kesehatan Republik Indonesia). But unfortunately the percentage of exclusive breastfeeding in Indonesia still does not meet the desired target, amounting to 54.3% with a target desired by 75%. The level of knowledge and maternal employment status is a factor affecting exclusive breastfeeding for the mother is still a lack of understanding about the practice of exclusive breastfeeding and busy mother because of her job. Therefore, the purpose of this study was to determine the relationship between level of knowledge and employment status with exclusive breastfeeding. This study used a quantitative research with research methods correlational. The study design used is cross sectional. Samples are mothers with babies aged 6 months. The sampling technique used the total population and obtained a number of 31 respondents. The results showed that there was a relationship between the level of knowledge with exclusive breastfeeding, the value of p = 0.022. There is a relationship between employment status with exclusive breastfeeding, the value of p = 0.023.